The Impact of Internet Access on Innovation and Entrepreneurship in Africa - Houngbonon, Georges Vivien (Washington, DC: World Bank, 2022)
This paper investigates the effects of access to high-speed internet on innovation and entrepreneurship in Africa. The identification strategy exploits the staggered arrival of submarine internet cables to the coast of Africa and the subsequent rollout of terrestrial fiber network across the continent. The findings show a positive effect of access to high-speed internet on innovation at the firm level, with availability of digital skills within the firm playing a key role in the internet-innovation nexus. The paper also finds evidence of internet-induced entrepreneurship: the probability that a household establishes a non-farm business increases when connected to the internet. However, the increase in entrepreneurial activities is largely concentrated in the service sector.